Comparative Study of Short-Term Efficacy and Safety of Mitomycin versus Lobaplatin for Hyperthermic Intraperitoneal Chemotherapy after Radical Surgery in Colorectal Cancer with High-Risk Factors for Peritoneal Carcinomatosis: A Propensity Score Matching Analysis - Xikai Guo; Yao Lin; Chu Shen; Yuan Li; Fan Xiang; Tuo Ruan; Xinyu Zeng; Jianbo Lv; Kaixiong Tao; Chuanqing Wu (Current Oncology, 2023)
Background: The drug selection of radical surgery (RS), with hyperthermic intraperitoneal chemotherapy (HIPEC), in pT4 colorectal cancer (CRC) remains controversial. Methods: Adverse events after HIPEC were estimated by common terminology criteria for adverse events version 5.0. The efficacy was evaluated using overall survival (OS) and recurrence-free rate (RFR). Propensity score matching (PSM) was used to reduce the influence of confounders between Mitomycin and Lobaplatin groups. Results: Of the 146 patients, from April 2020 to March 2021, 47 were managed with mitomycin and 99 with lobaplatin. There was no significant difference in the incidence of all adverse events between the two groups after PSM. OS and RFR were not significantly different between the two groups at 22 months (p = 0.410; p = 0.310). OS and RFR of the two groups also showed no significant difference for patients with T4a or T4b stage, tumor size < or ≥ 5 cm. Among patients with colon cancer, RFR at 22 months of the two groups was significantly different (100.0% vs. 63.2%, p = 0.028). Conclusions: In summary, the safety of mitomycin and lobaplatin for HIPEC was not different. Compared with lobaplatin, mitomycin for HIPEC after RS could benefit patients with colon cancer in RFR.